Pengaruh Penggunaan Sistem Bioflok pada Produktivitas dan Kelayakan Usaha Pembesaran Ikan Lele Konsumsi di Kota Pontianak - Aisyiah, Nur; Kurniati, Dewi; Maswadi, Maswadi (Universitas Galuh, 2024)
Catfish is one of the many fresh water fishes with high potential for farming in Pontianak. It also has high economic value. Increasing demand for catfish forced its farmers to also further increase their productivity. Methods of farming catfish have always been developed to fufill that goal. One of which is with biofloc system. Catfish farming using biofloc system is a catfish-raising system with the help of purposefully-grown microorganism which functions as detritivore, processing catfish farming waste. The biofloc can then be used as natural source of food for the catfish. It can be accelerated by inserting non-pathogenic bacterial culture of probiotic paired with aerator as both an oxygen supplier and air distributor. The purpose of this study is to gauge the productivity, production cost, and take of business with and without biofloc system and eligibility of catfish farming with and without biofloc system to develop and increase its quality, especially in Pontianak. The number of respondents is 86 samples, calculated using the Slovin method. Productivity of catfish farming with biofloc system is 56,88 kg/m2 with an average production cost as much as Rp 20.594.400,23 a year and an avegare take reaching Rp 26.340.593,02. Catfish farming business with bifloc system is eligible for development.